Glycobiology of Neuroblastoma: Impact on Tumor Behavior, Prognosis, and Therapeutic Strategies - Berois, Nora; Osinaga, Eduardo (Frontiers in Oncology, 2014)
Neuroblastoma (NB), accounting for 10% of childhood cancers, exhibits aberrant cell-surface glycosylation patterns. There is evidence that changes in glycolipids and protein glycosylation pathways are associated to NB biological behavior. Polysialic acid (PSA) interferes with cellular adhesion, and correlates with NB progression and poor prognosis, as well as the expression of sialyltransferase STX, the key enzyme responsible for PSA synthesis. Galectin-1 and gangliosides, overexpressed and actively shedded by tumor cells, can modulate normal cells present in the tumor microenvironment, favoring angiogenesis and immunological escape. Different glycosyltransferases are emerging as tumor markers and potential molecular targets. Immunotherapy targeting disialoganglioside GD2 rises as an important treatment option. One anti-GD2 antibody (ch14.18), combined with IL-2 and GM-CSF, significantly improves survival for high-risk NB patients. This review summarizes our current knowledge on NB glycobiology, highlighting the molecular basis by which carbohydrates and protein-carbohydrate interactions impact on biological behavior and patient clinical outcome.